2004
DOI: 10.1093/ajcn/79.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Edentulism and nutritional status in a biracial sample of well-functioning, community-dwelling elderly: the Health, Aging, and Body Composition Study

Abstract: Edentulism was associated with differences in the nutritional status of well-functioning, community-dwelling elderly, more so in whites than blacks. Edentate elders may benefit from dental, medical, and nutrition interventions targeted to addressing these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
118
3
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 50 publications
15
118
3
5
Order By: Relevance
“…Edentulous older people could only consume overcooked boiled rice as their main food, which is a good source of vitamin B 1 . Edentulism is not associated with total energy or food intake, but rather with the food groups consumed 20 . Since folate deficiency is associated with the pathogenesis of atherosclerotic lesions, our results accordingly revealed that male gender, history of heart disease, lower high-density lipoprotein and haematocrit were independent risk factors of folate deficiency.…”
Section: Discussionmentioning
confidence: 89%
“…Edentulous older people could only consume overcooked boiled rice as their main food, which is a good source of vitamin B 1 . Edentulism is not associated with total energy or food intake, but rather with the food groups consumed 20 . Since folate deficiency is associated with the pathogenesis of atherosclerotic lesions, our results accordingly revealed that male gender, history of heart disease, lower high-density lipoprotein and haematocrit were independent risk factors of folate deficiency.…”
Section: Discussionmentioning
confidence: 89%
“…Taichhi et al have carried out research in order to clarify the role of artificial dental arches for the process of swallowing in edentulous patients, the role of tongue for the smooth passage of food bolus to the oropharynx and the lifting of the larynx when placing the mandible in the intercuspal position. Edentulous patients tend to reduce the intake of fruits, vegetables and fiber and increase the intake of saturated fat compared to similar patients with recovered dentition (7,8,9). The functional difficulties associated with eating are to be regarded as the primary incentive for prosthetic recovery of missing teeth, otherwise prosthetic treatment per se would have no effect on positive dietary changes (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…26 Preserving teeth in good condition is not only restricted to the quality of life of the elderly but is an indicator of general health. [2][3][4] Edentulism is related to the deterioration in the systemic health of the aged 27 and is associated with reduced quality of life. 28 A Ac ck kn no ow wl le ed dg ge em me en nt ts s…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…4 Edentulism is an independent risk factor for significant weight loss 5 and is associated with systemic and chronic diseases among the elderly, becoming an important public health issue as a large proportion of elderly people are edentulous. 2 Tooth loss is mainly attributed to dental caries and gum disease.…”
mentioning
confidence: 99%